Health Communication Strategies for Wolbachia Mosquito Implementation in Dengue Prevention: A Case Study in Bontang City - Suraji Heri Prasetiyo; Pawito Pawito; Likha Sari Anggreni (Poltekita: Jurnal Ilmu Kesehatan, 2025)
Dengue Hemorrhagic Fever (DHF) remains a serious public health issue in Indonesia. One of the innovations developed to reduce the number of DHF cases is the implementation of Wolbachia-infected Aedes aegypti mosquitoes. This study aims to describe and evaluate the health communication strategies used in the implementation of Wolbachia mosquitoes in Bontang City, East Kalimantan The study employs a qualitative case study design, using four Focus Group Discussions (FGDs) with 32 participants, including community health volunteers (cadres, i.e. community health volunteers), household foster parents, sub-district officials, and health center staff. Thematic analysis was conducted with source triangulation to ensure data validity based on community perceptions, the socialization process, implementation challenges, and stakeholder support.. The results indicate mixed outcomes: positive acceptance was initially supported by trust in health workers, clear explanations of Wolbachia’s biological role, and active involvement of community volunteers; however, several obstacles reduced support, including ongoing dengue cases, perceived increase in mosquito populations, misinformation and hoaxes on social media, weak cross-sector coordination, and cadre turnover without transition. Discontinuous communication strategies weakened the effectiveness of health message delivery to the community. Strengthening risk communication, broader public campaigns, and routine cross-sector evaluations are needed to ensure the program’s sustainability.